Genetic testing for the long QT syndrome: who and why? Insights for clinical management - Schwartz, Peter J. (SA Heart Journal, 2017)
This article deals with a specifi c issue of growing importance for cardiologists or internists who happen to have to take care of a patient affected by the congenital long QT syndrome (LQTS), namely when to consider to request a genetic test. The focus is on who are the patients for whom genetic screening should be requested and why. One often ignored issue is also discussed, the potentially very serious consequences – for the patient and also for the doctor – of omitting genetic screening. The bottom line is that genetic screening for LQTS can no longer be regarded as a research tool but is an integral part of current medical management of this life-threatening but highly treatable disorder.